Ethnobotanical study of medicinal plants and their threats in Yeki district, Southwestern Ethiopia - Ashebir Awoke; Yared Siyum; Derbew Awoke; Habtamu Gebremedhin; Afework Tadesse (Journal of Ethnobiology and Ethnomedicine)
Abstract Background Ethiopia is recognized as a significant center of origin for a wide variety of plant species, particularly those with medicinal properties. A substantial segment of the population across the nation depends on these therapeutic plants for their primary healthcare needs. Many communities, both rural and urban, engage in traditional medicine practices, passing down their knowledge orally from one generation to the next. Consequently, this study was undertaken to record the traditional medicinal plants and the related indigenous knowledge in the Yeki district of Southwest Ethiopia. Methods Between March 2024 and August 2024, semi-structured interviews, in-person meetings, group discussions, and escorted field trips were used to gather quantitative ethnobotanical data. A total of 132 informants 100 men and 32 women were interviewed in order to gather ethnobotanical data. The informant consensus factor (ICF), fidelity level (FL), plant part value, preference ranking, and direct matrix ranking were among the quantitative techniques that were employed. Furthermore, the study used a variety of statistical tests, such as independent t-tests, one-way ANOVA, correlation, and regression with R software version 4.3.2, to compare the ethnobotanical knowledge of various informant groups. Result A total of 98 species of traditional medicinal plants from 81 genera and 45 plant families were identified in the current study. The Asteraceae (11 species) were the largest family used by local peoples, followed by Solanaceae (8 species). The most commonly used plant parts were leaves and roots, and the primary technique for making remedies was crushing. The respiratory systems disease categories had the second highest consensus score (ICF: 0.90), after the dermal disease category (ICF: 0.91). The number of medicinal plants reported by respondents across gender, age groups, educational level, and informant’s type varied significantly (P < 0.05). Various medicinal species can be found in the area’s vegetation, but they are threatened by deforestation, agricultural extension, firewood, modernization, IAS, charcoal production, and material culture. Conclusion The results highlight the extensive variety of medicinal plants and the accompanying traditional knowledge present in the Guraferda district. The elevated ethnobotanical indices justify the need for additional phytochemical and pharmacological research. It is advisable to implement integrated conservation strategies to tackle the challenges confronting these precious plant resources.